Biomimetic and Biohybrid Systems c - Lepora, Nathan F.; Mura, Anna.; Krapp, Holger G.; Verschure, Paul F. M. J.; Prescott, Tony J.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the refereed proceedings of the second International Conference on Biomimetic and Biohybrid Systems, Living Machines 2013, held in London, UK, in July/August 2013. The 65 revised full papers presented were carefully reviewed and selected from various submissions. The papers are targeted at the intersection of research on novel live-like technologies inspired by scientific investigation of biological systems, biomimetics, and research that seeks to interface biological and artificial systems to create biohybrid systems
Keywords: Computer science; Artificial intelligence; Computer vision; Optical pattern recognition; Computer Science; Artificial Intelligence (incl. Robotics).; Computation by Abstract Devices; Pattern Recognition; Information Systems Applications (incl. Internet).; Image Processing and Computer Vision; Control, Robotics, Mechatronics